Outcomes in patients with acute pulmonary embolism and patent foramen ovale: Findings from the RIETE registry. Issue 202 (June 2021) - Lacut, K.; Le Moigne, E.; Couturaud, F.; Font, C.; Vázquez, F.J.; Cañas, I.; Díaz-Peromingo, J.A.; Gil-Díaz, A.; Bucherini, E.; Monreal, M.; ,
Abstract: Introduction: An increased risk of ischemic stroke in patients with acute pulmonary embolism (PE) and patent foramen ovale (PFO) was reported but few data exist regarding prognostic outcomes of those patients. Material and methods: Using data in the RIETE registry, we compared the characteristics, therapeutic approaches and outcomes of patients with PE according to the presence or absence of PFO. Results: From August 2016 to January 2020, 4148 patients with acute PE were enrolled. Of these, 2775 (67%) had no transthoracic echocardiogram (TTE), 993 (24%) underwent TTE but had no reported results on PFO. Among the remaining 380 patients, 287 (74%) did not have PFO and 93 (26%) had PFO. Patients with PFO were more likely to have chronic heart failure, prior myocardial infarction or ischemic stroke than those without PFO. Patients with PFO had a higher rate of subsequent ischemic stroke than those without PFO (hazard ratio (HR): 9.28; 95% CI: 1.83–69.1), than those with TTE but no data on PFO (HR: 10.1; 95% CI: 2.56–42.4) or without TTE (HR: 9.78; 95% CI: 3.02–28.4). On multivariable analysis, patients with PFO were at increased risk for subsequent ischemic stroke than those without PFO (HR: 8.96; 95% CI: 1.68–47.7). Conclusions: PFO was searched in a minority of patients with an acute PE in real life setting. Subject to possible selection and measurement biases, our results confirmed a higher risk of ischemic stroke in PE patients with PFO compared to those without PFO. This association warrants further investigation before determining the best therapeutic option in patients with acute PE and concomitant PFO. Highlights: In real life setting, patent foramen ovale (PFO) was searched in a minority of patients with acute pulmonary embolism (PE) When PFO was searched, PFO was present in one in every four patients Patients with PFO were at a 9-fold higher risk to develop ischemic stroke early in the course of anticoagulation They also had a higher rate of PE recurrences than those without PFO These results confirmed the poor prognosis of patients with acute PE and PFO